Increasing the activity of immobilized enzymes with nanoparticle conjugation. (August 2015) - Ding, Shaowei; Cargill, Allison A; Medintz, Igor L; Claussen, Jonathan C
Graphical abstract: Highlights: Enzyme activity/stability can be improved upon immobilization on nanoparticles (NPs). Five underlying physicochemical mechanisms describe enzyme–NP activity. Carbon, metal, and polymeric nanomaterials as well as quantum dots can be enzyme carriers. Applications of enzyme–NPs include sensing, energy production, and drug delivery. Abstract : The efficiency and selectivity of enzymatic catalysis is useful to a plethora of industrial and manufacturing processes. Many of these processes require the immobilization of enzymes onto surfaces, which has traditionally reduced enzyme activity. However, recent research has shown that the integration of nanoparticles into enzyme carrier schemes has maintained or even enhanced immobilized enzyme performance. The nanoparticle size and surface chemistry as well as the orientation and density of immobilized enzymes all contribute to the enhanced performance of enzyme–nanoparticle conjugates. These improvements are noted in specific nanoparticles including those comprising carbon (e.g., graphene and carbon nanotubes), metal/metal oxides and polymeric nanomaterials, as well as semiconductor nanocrystals or quantum dots.